Coccidioidal meningitis and neurosyphilis co-infection in a non-HIV patient - Kim, Jani M.; Sivasubramanian, Geetha (Medical mycology case reports, 2021)
Coccidioides sp. and Treponema pallidum can both cause infections of the central nervous system if untreated. We describe a case of an immunocompetent patient living in an endemic region for Coccidioides who presented with headaches and diplopia and was found to have co-infection of coccidioidal meningitis and neurosyphilis. We highlight the importance of evaluation for CNS co-infections as they may be underdiagnosed, especially in endemic areas for coccidioidomycosis.